2016
DOI: 10.1152/ajpcell.00364.2015
|View full text |Cite
|
Sign up to set email alerts
|

STIM and ORAI proteins: crucial roles in hallmarks of cancer

Abstract: Intracellular Ca2+ signals play a central role in several cellular processes; therefore it is not surprising that altered Ca2+ homeostasis regulatory mechanisms lead to a variety of severe pathologies, including cancer. Stromal interaction molecules (STIM) and ORAI proteins have been identified as critical components of Ca2+ entry in both store-dependent (SOCE mechanism) and independent by intracellular store depletion and have been implicated in several cellular functions. In recent years, both STIMs and ORAI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 113 publications
(146 reference statements)
0
46
0
Order By: Relevance
“…The Ca 2+ -selective store-operated current (ICRAC) is mediated by the endoplasmic reticulum (ER) Ca 2+ -sensor STIM1 and the store-operated Ca 2+ (SOC) channel Orai1 but also the canonical transient receptor potential (TRPC) channel family, including TRPC1. In mammalian cells, several key components of SOCE have been described: STIM1-2, Orai1-3, and TRPC1-7; while in recent years, STIMs and ORAIs have been regarded as possible molecular targets for cancer diagnostic and therapeutics [47,49,50,51,52]. Anguita and Villalobo described in 2016 that there is a crosstalk between non-receptor Src-family kinases and the Ca 2+ transient generated in activated cells by a variety of extracellular and intracellular stimuli that might result in stimulation of signaling pathways [53].…”
Section: The Role Of [Ca2+]i Signaling In the Regulation Of Expresmentioning
confidence: 99%
“…The Ca 2+ -selective store-operated current (ICRAC) is mediated by the endoplasmic reticulum (ER) Ca 2+ -sensor STIM1 and the store-operated Ca 2+ (SOC) channel Orai1 but also the canonical transient receptor potential (TRPC) channel family, including TRPC1. In mammalian cells, several key components of SOCE have been described: STIM1-2, Orai1-3, and TRPC1-7; while in recent years, STIMs and ORAIs have been regarded as possible molecular targets for cancer diagnostic and therapeutics [47,49,50,51,52]. Anguita and Villalobo described in 2016 that there is a crosstalk between non-receptor Src-family kinases and the Ca 2+ transient generated in activated cells by a variety of extracellular and intracellular stimuli that might result in stimulation of signaling pathways [53].…”
Section: The Role Of [Ca2+]i Signaling In the Regulation Of Expresmentioning
confidence: 99%
“…Several studies have shown that the Ca 2+ toolkit, that is, all proteins involved in regulating Ca 2+ signaling, is often remodeled in cancer cells, particularly in PCa. This remodeling promotes sustained proliferation, reduced programmed cell death, and may lead to the acquisition of a metastatic phenotype and subsequent castration‐resistant status . In nonexcitable cells, Ca 2+ influx is partly mediated by Ca 2+ ‐selective channels activated by intracellular Ca 2+ store depletion called store‐operated channels (SOCs), and by store‐independent Ca 2+ channels, such as ARC channels (arachidonate‐regulated Ca 2+ channels) .…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of Orai1/STIM1, mostly by increasing SOCE, appears to enhance various cancer hallmarks . In breast cell lines, overexpression of Orai1/STIM1 and Orai3 is correlated with increased proliferation, migration, and increased metastatic potential . In contrast, it has been suggested that this Orai1/STIM1 couple is required for proapoptotic effects in LNCaP PCa cell lines .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations